2005
DOI: 10.1021/je050296u
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpies of Transfer of Amino Acids from Water to Aqueous Solutions of Alkali Metal Nitrates

Abstract: Enthalpies of solution of glycine, l-alanine, and l-serine in water and aqueous solutions of LiNO3, NaNO3, and KNO3 were measured at 298.15 K. Enthalpies of transfer (Δtr H) of amino acids from water to aqueous solutions of nitrate salts were derived. The effect of the ion type, concentration, and structure of amino acids on the magnitude of the transfer enthalpies are discussed in terms of the electrostatic interaction and the structural hydration interaction model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…[2][3][4] Amino acids and peptides, as model compounds of protein, are of fundamental importance in life system research. [5][6][7][8][9][10] Studies on the interaction between natural amino acids/peptides and sugar alcohols in water are helpful in understanding the essence of some biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Amino acids and peptides, as model compounds of protein, are of fundamental importance in life system research. [5][6][7][8][9][10] Studies on the interaction between natural amino acids/peptides and sugar alcohols in water are helpful in understanding the essence of some biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Administered as a hypertonic infusion solution, they enhance distal tubule delivery of Na + and water resulting in increased urine formation; i.e., they exhibit a diuretic effect . Sugars and polyols are well-known stabilizing agents in their native state. Amino acids and peptides, as model compounds of protein, are of fundamental importance in life system research. Studies on the interaction between natural amino acids/peptides and sugar alcohols in water are helpful in understanding the essence of some biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of enthalpies of solution were carried out on a RD496 microcalorimeter at 298.15 K, as previously described . The performance of the calorimeter and its reliability for the measurement were ascertained by determining the enthalpy of glycine (14.15 kJ·mol −1 ) in water, and the data compare well with literature data. , …”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of acid–base properties of amino acids is extremely important in understanding many properties of proteins . It is well-known that electrolytes influence the stability of proteins. , Some studies have revealed that the presence of an electrolyte drastically affects the behavior of amino acids and peptides in solutions, and this fact can be used for their separation and purification.…”
Section: Introductionmentioning
confidence: 99%